INDEPENDENT STRATUM FORMATION ON THE AVIAN SEX CHROMOSOMES REVEALS INTER‐CHROMOSOMAL GENE CONVERSION AND PREDOMINANCE OF PURIFYING SELECTION ON THE W CHROMOSOME. (29th August 2014) - Wright, Alison E.; Harrison, Peter W.; Montgomery, Stephen H.; Pointer, Marie A.; Mank, Judith E.
<x xml:space="preserve">Abstract</x> We used a comparative approach spanning three species and 90 million years to study the evolutionary history of the avian sex chromosomes. Using whole transcriptomes, we assembled the largest cross‐species dataset of W‐linked coding content to date. Our results show that recombination suppression in large portions of the avian sex chromosomes has evolved independently, and that long‐term sex chromosome divergence is consistent with repeated and independent inversions spreading progressively to restrict recombination. In contrast, over short‐term periods we observe heterogeneous and locus‐specific divergence. We also uncover four instances of gene conversion between both highly diverged and recently evolved gametologs, suggesting a complex mosaic of recombination suppression across the sex chromosomes. Lastly, evidence from 16 gametologs reveal that the W chromosome is evolving with a significant contribution of purifying selection, consistent with previous findings that W‐linked genes play an important role in encoding sex‐specific fitness.